Ranking of used cars brands and its criteria by using Fuzzy Topsis and Fuzzy Ahp / Nur Amira Shuhada Mohd Basri - Mohd Basri, Nur Amira Shuhada (2019)
Decision making on selection of used cars is quite difficult since there are many brands in the market and criteria such as price, engine speed, fuel systems, cost of ownership and safety provided by the car need to be considered. In addition, people do not buy a car or change their car frequently. Many multi-criteria decision making could be applied in this kind of problem. In this case study, Fuzzy Technique for Order Preference Similarity to Ideal Solution (TOPSIS) is applied to rank the brands of used cars and Fuzzy Analytic Hierarchy Process (AHP) is used to determine the most preferred criteria of used car. The primary data collected from the experts was analyzed. The findings show that PROTON is in the highest ranking while Toyota is in the lowest ranking. It also shows that fuel system is the most preferable criteria according to the buyers from decision makers’ perspectives.